Pemanfaatan Instagram @dolan.ngebel Sebagai Media Promosi Pariwisata Telaga Ngebel Ponorogo - Fathul Munggin; Andhita Risko Faristiana (Jurnal Multidisiplin Indonesia, 2024)
Instagram has become one of the effective social media platforms for tourism promotion due to its power in delivering attractive visual information. The Instagram account @dolan.ngebel utilizes this potential to introduce the Telaga Ngebel tourist destination in Ponorogo, East Java. The purpose of this study was to examine the marketing tactics used by the @dolan.ngebel account to make Telaga Ngebel more attractive and how effectively they work to attract more tourists to visit the area. The methods used were content analysis of Instagram account uploads and interviews with account managers. The results of the study showed that Instagram has been utilized as a means of promoting tourism in Telaga Ngebel Ponorogo through various forms and that Instagram is very effective in enhancing the image of Telaga Ngebel as an attractive tourist destination. High-quality photos, short stories included in the captions, and active interaction with followers can influence the interest of potential tourists. However, obstacles such as limited content, resources, and internet connections, low interaction with followers, lack of use of relevant hashtags, and limited understanding of Instagram features are often faced. The proposed solutions include careful content planning, creative skills training, collaboration with professionals, utilization of supporting technology, and content diversification to increase engagement.